The species of Brasema Cameron, 1884 (Hymenoptera, Eupelmidae) associated with oak gall wasps (Hym., Cynipidae, Cynipini) in North America with the description of two new species from México - Cazorla-Vila, Júlia; Gibson, Gary A. P.; García-Martiñón, Rosa Delia; Clark-Tapia, Ricardo; Barrera-Ruíz, Uriel M.; Mederos, Jorge; Equihua-Martínez, Armando; Estrada-Venegas, Edith; Cuesta-Porta, Victor; Pujade-Villar, Juli (Zootaxa, 2026)
Eight species of Brasema Cameron, 1884 (Hymenoptera, Eupelmidae) associated with galls of Cynipini (Hymenoptera, Cynipidae) in North America are keyed and illustrated through macrophotography. The gender of Brasema is here treated as neuter rather than feminine and the reasons for this are given. Brasema mexicanum Cazorla-Vila & Pujade-Villar sp. nov. and Brasema obscurum Cazorla-Vila & Pujade-Villar sp. nov. are described from México emerging from different cynipid oak galls belonging to Quercus and Lobatae sections. Males and females of these new species are illustrated through macrophotography and scanning electron micrographs. The new species are supported as new by morphological and molecular evidence. New oak gall wasp hosts are recorded for B. auratum (Ashmead, 1886), B. dryophantae (Ashmead, 1886), B. macrocarpae (Ashmead, 1888) and B. speciosum (Girault, 1916). Distribution of B. macrocarpae and B. speciosum are expanded in USA and México, and B. flavovariegatum (Ashmead, 1888) and B. gemmarii (Ashmead, 1886) in the USA. A phylogenetic analysis of COI was carried out with 7 sequences of the two new Mexican species plus 64 sequences available from BOLD belonging to 21 identified and unidentified morphospecies to obtain the first Brasema phylogeny.